Desafíos Legales en la Pericia Informática en Ecuador: Análisis de la Efectividad del Informe Pericial en Casos de Delitos Informáticos - Romero Sánchez, Wilman Daniel (2024)
Before pursuing a law degree, the student authored the following paper: “Legal Challenges in Computer Expertise in Ecuador: An analysis of the Effectiveness of the Expert Report in Cases of Computer Crimes”. It proposes a legal and doctrinal analysis of expert reports in computer crimes, considering accelerated globalization and the growing incidence of cybercrimes in Ecuador. As a consequence of globalization, cybercrime has become a widespread phenomenon affecting individuals and legal entities alike. Thus, the following work of curriculum integration emphasizes the importance of adapting to technological and communication advances in order to compete effectively in today's globalized world. As regards cybercrime in Ecuador, there has been a significant increase in computer crimes, which highlights the need for updated legal regulations and protocols, particularly concerning expert reports. Despite Ecuadorian legislation regulating legal experts' activities, there are concerns that the regulations governing expert reports are outdated and lack international methodologies for guiding the creation of computer expert opinions. It also highlights the need to apply international standards, such as UNE 197010:2015, in the preparation of computer expert reports to ensure their quality and validity. During the development of this curricular integration project, a variety of resources were used, such as: research methodologies and techniques, which were explained in the respective proposal. This included conducting interviews and surveys with legal professionals. The purpose of the research is to determine whether the international standard UNE 197010:2015 can be applied in computer crime expert reports, as well as to demonstrate the inadequacy of the Judiciary Council's methodology. Additionally, this Curricular Integration Work is intended to serve as a reference for future research and as support material for legal professionals and procedural parties involved in cybercrime cases.